Children of the stars : a novel - Escobar, Mario, 1971- (Thomas Nelson, 2020)
August 1942. Jacob and Moses Stein, two young Jewish brothers, are staying with their aunt in Paris amid the Nazi occupation. The boys<U+2019> parents, well-known German playwrights, have left the brothers in their aunt<U+2019>s care until they can find safe harbor for their family. But before the Stein's can reunite, a great and terrifying roundup occurs. The French gendarmes, under Nazi order, arrest the boys and take them to the Vélodrome d<U+2019>Hiver, a massive, bleak structure in Paris where thousands of France<U+2019>s Jews are being forcibly detained. Jacob and Moses know they must flee in order to survive, but they only have a set of letters sent from the south of France to guide them to their parents. Danger lurks around every corner as the boys, with nothing but each other, trek across the occupied country. Along their remarkable journey, they meet strangers and brave souls who put themselves at risk to protect the children, some of whom pay the ultimate price for helping these young refugees of war.